2015
DOI: 10.1039/c5cc06983a
|View full text |Cite|
|
Sign up to set email alerts
|

NanoSIMS analysis of an isotopically labelled organometallic ruthenium(ii) drug to probe its distribution and state in vitro

Abstract: The in vitro inter- and intra-cellular distribution of an isotopically labelled ruthenium(II)-arene (RAPTA) anti-metastatic compound in human ovarian cancer cells was imaged using nano-scale secondary ion mass spectrometry (NanoSIMS). Ultra-high resolution isotopic images of (13)C, (15)N, and Ru indicate that the phosphine ligand remains coordinated to the ruthenium(II) ion whereas the arene detaches. The complex localizes mainly on the membrane or at the interface between cells which correlates with its anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Secondary ion maps of 13 C 12 C − / 12 C 2 − , 14 N 12 C − / 12 C 2 − , 15 N 12 C − / 14 N 12 C − , 31 P − / 12 C 2 − , 34 S − / 12 C 2 − , and 102 Ru − / 12 C 2 − , as well as transmission electron microscopy (TEM) images of MDA-MB-231 cells treated with 15 N/ 13 C-labelled RAPTA-T (500 μM, 24 h), are shown in Figure 1 . As observed previously in A2780CR cells treated with 15 N+ 13 C-labelled RAPTA-T [ 17 ], 13 C enrichment was not observed in RAPTA-T treated MDA-MB-231 and MCF-7 cells indicating that the sample preparation dilutes the 13 C-isotopic enrichment from the 13 C-enriched toluene ligand to below the detection limit [ 20 ]. In the MDA-MB-231 cells, all Ru hotspots found were co-enriched with 15 N ( Figure 1 , green boxes), suggesting that the phosphine (PTA) ligand remains coordinated to the Ru centre.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Secondary ion maps of 13 C 12 C − / 12 C 2 − , 14 N 12 C − / 12 C 2 − , 15 N 12 C − / 14 N 12 C − , 31 P − / 12 C 2 − , 34 S − / 12 C 2 − , and 102 Ru − / 12 C 2 − , as well as transmission electron microscopy (TEM) images of MDA-MB-231 cells treated with 15 N/ 13 C-labelled RAPTA-T (500 μM, 24 h), are shown in Figure 1 . As observed previously in A2780CR cells treated with 15 N+ 13 C-labelled RAPTA-T [ 17 ], 13 C enrichment was not observed in RAPTA-T treated MDA-MB-231 and MCF-7 cells indicating that the sample preparation dilutes the 13 C-isotopic enrichment from the 13 C-enriched toluene ligand to below the detection limit [ 20 ]. In the MDA-MB-231 cells, all Ru hotspots found were co-enriched with 15 N ( Figure 1 , green boxes), suggesting that the phosphine (PTA) ligand remains coordinated to the Ru centre.…”
Section: Resultssupporting
confidence: 53%
“…An approach that produces visual distribution maps of metal-based drugs in cells, nanoscale secondary ion mass spectrometry (NanoSIMS) [ 15 ] is attracting increasing attention [ 16 ] and has been used to image RAPTA-T in cisplatin-resistant human ovarian cancer (A2780CR) cells [ 17 ]. Consequently, the aim of the present study is to determine the distribution of RAPTA-T in MDA-MB-231 and MCF-7 cells and to probe whether any difference in distribution exists between these cells possessing different metastatic phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…NanoSIMS allows high spatial resolution imaging (B100 nm) of the metal centre and when used in tandem with isotopic labelling, provides valuable information on the ligands surrounding the metal centre. 17,18 In recent years, NanoSIMS has been used to study cellular distribution of metallodrugs based on Au, 19 Ru 17 and Pt, [20][21][22] with the cellular distribution of cisplatin being reported in colon cancer cells. Despite the high spatial resolutions of this technique, as far as we are aware no comparative study has been done to analyse with high spatial resolution differences in the distribution of Pt between cancer cells that are sensitive and resistant to the drug.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Interestingly, RAPTA-C also exhibits anti-angiogenic activity, which was demonstrated in the human colorectal carcinoma (LS174T) grown on the CAM, a predictive preclinical model used in acute toxicological studies for anti-cancer or anti-angiogenic treatments. [83] Moreover, 24 hours after in vivo PDT-induced angiogenesis, [85,86] RAPTA-C has been applied onto the treated area, and it has been demonstrated that application of the drug after PDT inhibits vessel re-growth. [83] Moreover, 24 hours after in vivo PDT-induced angiogenesis, [85,86] RAPTA-C has been applied onto the treated area, and it has been demonstrated that application of the drug after PDT inhibits vessel re-growth.…”
Section: Side Effectsmentioning
confidence: 99%